Disentangling the physical, social, and situational contexts of young adolescents' initiation to alcohol use and intoxication: A mixed methods study. (1st September 2022) - Islam, Sabrina; Kaner, Emily; Price-Wolf, Jennifer; Grube, Joel W.; Lipperman-Kreda, Sharon
Abstract: Background: The onset of alcohol use during adolescence is associated with concurrent and subsequent related problems. Research on drinking contexts that underly these key first-time experiences and how they differ by initiation type is needed. The current study examined the physical, social, and situational characteristics of three types of initiation: first drink, first heavy episodic drinking (HED), and first intoxication and considered variations between early and later initiating adolescents. Methods: A mixed-methods approach was used to survey and interview adolescents who reported lifetime drinking. Survey responses from 471 participants were analyzed using multilevel multinomial and logistic regressions accounting for nesting of drinking events (i.e., type of initiation) within respondents. A subsample of 50 participants recruited at baseline took part in-depth interviews that were thematically coded. Results: After controlling for demographics, initiation of HED and intoxication, compared to initiation of a whole drink, were more likely to occur when more close friends are present and when those close friends are also drinking. The likelihood of early initiation of a whole drink and intoxication was also positively associated with being in an outdoor setting. Narratives identified distinct and shared patterns of context characteristics across the types of alcohol initiation. Conclusion: The quantitative and qualitative findings revealed several parallels as well as aspects that differ, enriching our understanding of early drinking contexts. Results highlight the importance of considering contextual characteristics by initiation type for prevention efforts. Highlights: Contexts were examined for three types of alcohol initiation: whole drink, heavy episodic drinking, and intoxication. Physical, social, and situational context characteristics were uniquely associated with initiation type. Adolescents explained the role of these contexts when considering their initiation of alcohol use. Results suggest distinguishing initiation type for prevention.